Endoscopic retrograde cholangiopancreatography in children with pediatric congenital biliary dilatation associated with pancreatobiliary maljunction: experience from a tertiary center - Giovanni Rollo; Valerio Balassone; Simona Faraci; Filippo Torroni; Luigi Dall'Oglio; Paola De Angelis; Tamara Caldaro (Frontiers in Pediatrics)
BackgroundCongenital biliary dilatation (CBD) is a congenital malformation of the main biliary tract usually associated with the pancreatobiliary maljunction (PBM), determining stone formation, cholangitis, pancreatitis, and cholangiocarcinoma. The role of endoscopic retrograde cholangiopancreatography (ERCP) in treatment and diagnosis has not been established yet. Therefore, the aim of our study is to define the actual role of ERCP in children with CBD.MethodsA retrospective review of consecutive patients with congenital biliary dilatation undergoing preoperative ERCP and subsequent surgical treatment at our pediatric tertiary referral center (Endoscopy and Digestive Surgery, Bambino Gesù Children's Hospital, IRCCS, Rome, Italy) was performed between 2012 and 2023.ResultsA total of 31 patients were included in the present study. Preoperative ERCP detected a PBM in 28 patients (90%). According to Todani's classification, 2 patients (6.5%) had choledochal cyst (CC) type IV, and 29 patients (93.5%) were diagnosed with CC type I. In 18 (58%) patients, ERCP was performed for treating acute pancreatitis. Sphincterotomy could be performed in 23 of 31 (74%) patients. Patients who did not undergo sphincterotomy had a higher number of acute episodes while awaiting surgery.ConclusionsThe present study is supportive of an essential role of ERCP in the diagnostic and preoperative management of children with CBD with acute presentation or inconclusive magnetic resonance cholangiopancreatography findings.